Editorial on Special Issue “Pharmacokinetics, Pharmacodynamics, and Drug Interactions” - Zhu Zhou (Pharmaceutics)
Pharmacokinetics describes the absorption, distribution, metabolism, and excretion of a drug, while pharmacodynamics focuses on the effects of the drug on the body [...]